Koala Lou - Fox, Mem, 1946-; Lofts, Pamela (Orlando : Harcourt Brace, 1989)
A young koala, longing to hear her mother speak lovingly to her as she did before other children came along, plans to win her distracted parent's attention.
Wilson's Children, October 2010.
School Library Journal, June 2000.
Booklist, May 1996.
Horn Book, May 1997.
4.3
K-3
Keywords: Mother and child -- Fiction; Koala -- Fiction; Mother-child relationship -- Fiction; Koalas -- Fiction; Mother and child -- Fiction; Koala -- Fiction